Senescence rates are determined by ranking on the fast-slow life-history continuum. - Jones, O; Gaillard, J; Tuljapurkar, S; Alho, J; Armitage, K; Becker, P; Bize, P; Brommer, J; Charmantier, A; Charpentier, M; Clutton-Brock, T; Dobson, F; et al. (2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar-sized birds. These generalizations have been challenged because of limitations of life-table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual-based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life-table approach. Focusing on one aspect of life history - survival or recruitment - can provide reliable information on overall senescence.